Menyatukan Empat Pilar Kurikulum: Upaya Integratif Dalam Menjamin Mutu Pendidikan - Fauzan, Ahmad; Agus Pahrudin; Sri Rahmi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This article aims to examine the integration of the four main components of the curriculum objectives, content, instructional strategies, and evaluation, in order to enhance the quality and effectiveness of education in Indonesia. The primary focus of this study is to explore how the synergy among these components supports the implementation of the Merdeka Curriculum and the development of a holistic, character-based education. This research employs a qualitative descriptive method through a literature review approach. Data were collected from eight relevant national journal articles discussing the concepts, practices, and evaluations of curriculum integration across various educational levels. The analysis was conducted using comparative and interpretative techniques to synthesize findings. The study reveals that successful curriculum implementation highly depends on the coherence between educational goals, the relevance of learning materials, context-based teaching strategies, and comprehensive evaluation systems. Fragmentation among curriculum components tends to result in partial and ineffective educational practices. Therefore, an integrative curriculum model is urgently needed to unify these four components in both curriculum design and classroom implementation. This model is recommended as a strategic approach in the ongoing national curriculum reform.